(3TQM Cdajg GHf eGdcs - (3HOQ GdOjf CHh YHO Gddg eMeO Hf eMeO Hf eGdc , GHf GdfGXes; (3eMeO Hf YHO Gddg, GHf eGdc GdWGFj GdLqjGfj, CHh YHO Gddg, LeGd GdOjf,J (B672 (3g` s
(3ChdgG (B:s
(3bGd GdTjN GdEeGe HOQ GdOjf CHh YHO Gddg eMeO Hf eGdc GdWGFi CeG HYO MeO Gddg HeGdg ef GdeMGeO aEfi PGcQ ai gPG GdcJGH CQLhRI hGdOi ai Yde GdfMh s
(3BNQgG (B:s
(3hBdg GdZQ GdcQGe GdHQQI hUMHg GdefJNHjf GdNjQI aGYde Cfg bO GfJgi ZQVg ef gPG GdfXe hGfg bOETJed Ydi CYXe GdeYeeGJ ef Yde GdYQHjI MJi NJe GdcJGH HMeO Gddg hGdMeO ddg QH GdYGdejf s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHJ ajg CHjGJ GdCdajI HGdMeQI hGdTQM HeOGO CShO Hbde Objb s
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdfMhs